Strategy Analysis in Improving the Work Quality of Regional Office Employees of the Ministry of Religion of North Sumatra Province - Diah Larasati; Sri Sudiarti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Competition between companies in the era of globalization is getting sharper, human resource development is the main way to win global competition. Companies need quality human resources who produce good quality work. This study aims to find out what strategies are needed to improve the quality of employee work at the Regional Office of the Ministry of Religion of North Sumatra Province, and to determine the extent to which the quality of work of employees at the Ministry of Religion of North Sumatra, especially in the Finance section.